Conception of personal pronouns in a multi-racial society - Setia, Roszainora; Ghazali, Siti Norliana; Mustapha, Aida; Jusoff, Kamaruzaman; Abdullah, Farhah (Canadian Academy of Oriental and Occidental Culture, 2009)
Learning grammar for most people especially ESL learners is a daunting and difficult task. It is especially true in Malaysia where students find English grammar difficult to comprehend. Interference from major ethnic groups’ mother tongues play a great influence in shaping the students’ attitudes and understandings of the English grammar including personal pronouns. This study tried to ascertain which aspects of personal pronouns that multi- ethnic students find most difficult and it hypothesized that different ethnic groups will produce different results. Even though all groups had the basic knowledge in using personal pronouns, they got confused when it came to having object pronouns taking the role of what they thought as an acceptable and common everyday usage of subject pronouns. One problematic area faced by the students in the use of personal pronouns was deciding on the correct pronoun to refer to plural third person (neuter) antecedents. There was a significant difference in the performance of a pronouns elicitation task between ethnic groups of students.